Reversibility of hydrolysis inhibition at high hydrogen partial pressure in dry anaerobic digestion processes fed with wheat straw and inoculated with anaerobic granular sludge - Cazier, Elisabeth A (Waste management (New York, N.Y.), 2019)
Copyright © 2019 Elsevier Ltd. All rights reserved.